HERMENEUTIKA M. AMIN ABDULLAH DAN KONTRIBUSINYA DALAM STUDI KEISLAMAN - El Mazir, Wildan; Elhady, Aminullah; Masrohatin, Siti (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
Qur'anic exegesis (tafsir) occupies a special place in the development of intellectual traditions and Islamic civilization at large. As the primary source of Islamic teachings, Muslims have, for centuries, strived to understand the various meanings of the Qur'an in ways that meet the needs of contemporary society through diverse methods, including hermeneutics. This article aims to discuss the hermeneutical approach used by M. Amin Abdullah in the discourse of Qur'anic interpretation. This study falls into the category of qualitative research using a library research method, in which data is derived from textual studies or books relevant to the topic under discussion. The data analysis technique employed in this research is content analysis, used to analyze written data in the form of communicative content. The results of this study reveal that M. Amin Abdullah's hermeneutics generally align with the broader study of hermeneutics. However, the methodological distinction of his approach lies in the epistemological foundation of an integrative-interconnective paradigm in Islamic studies. Due to this methodological distinction, M. Amin Abdullah's hermeneutics possess a unique character in producing meaning in the study of Qur'anic exegesis. Keywords: exegesis; Qur'an; hermeneutics